Potential of Jatropha Curcas Seeds oil for Polyester-amides Production - Akinsanoye, Olakunle Alex; Oginni, Abimbola Odunola; Omotoso , Mopelola Abeke (Journal of Physical Sciences, 2025)
Purpose: Jatropha curcas potential as feedstock for polyester-amides production was studied. Polyesteramides are valuable biomaterials in the activities of petroleum industries where they are utilized as oil field chemicals. Methodology: Jatropha curcas fruits were collected in Ibadan and its environment. Seed oil of this fruit was extracted using n-hexane and concentrated. The phenol Jatropha curcas biopolymer (PJCB) and cresol Jatropha curcas biopolymer (CJCB) were prepared by polymerizing the oil with phenol and cresol via cationic polymerization method. Polyacrylamide (PAA) was prepared through free radical polymerization technique. Polyester-amides were prepared by polymerizing PJCB, CJCB and polyacrylamide (PAA). They were characterized using FTIR for functional groups modifications, 1H-NMR for changes in the chemical environments and Viscometry techniques for mean molecular weight determination. Findings: The oil yield is 55.60%. Iodine value (gI2/100g) is 105.33±1.78, 97.32±0.01, 101.33±0.66 for oil, PJCB and CJCB respectively. FTIR band shifts at 1649.48cm-1 and 1600.35cm-1 confirm C=C stretch of aromatics in PJCB and CJCB. PAA formation was confirmed with C=O stretch at 1680.00cm-1. Peaks at 3234.28cm-1 and 3097.14cm-1 assigned to N-H stretching vibration of amides confirmed polyester-amide. The 1H-NMR spectra showed peaks at δppm, 7.25 and 7.06 indicating aromatics for the PJCB &CJCB. δppm at 7.18 confirms amide protons in PAA. δppm 6.86 and 8.69 confirm amide formation while peaks at δ2.36ppm and δ3.11ppm were evidences for ester formation. These peaks confirm the new materials as polyester-amides. The mean molecular weight (g/mol) for PJCB, PJCB-PAA, CJCB and CJCB-PAA are 1.041x109, 1.39187x1012 9.929x109 and 1.07919 x 1012 respectively. Unique Contribution to Theory, Practice and Policy: Jatropha curcas oil is viable in formulating polyester-amides for industrial usages.